Un viaje sanador (2017)
This paper presents a reflection by three teachers from Instituto Pedagógico Nacional about the relevance of expeditionary trips in the life of the teachers of the country, after taking part in an idep Systematization Project in the context of the Teacher Qualification component, which allowed following on-site experiences, thus generating an exchange of experiences between groups of teachers from schools in Bogotá and schools in other regions of the country. The reflection is about the chronicles of a trip made to Medellín, where the exchange allowed the teachers to “heal” through the pedagogical and cultural exchange.